2023
DOI: 10.1002/ejic.202200735
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cobalt(III) Cage Complexes as Inhibitors of the Mitochondrial Calcium Uniporter

Abstract: The mitochondrial calcium uniporter (MCU) mediates uptake of calcium ions (Ca 2 + ) into the mitochondria, a process that is vital for maintaining normal cellular function. Inhibitors of the MCU, the most promising of which are dinuclear ruthenium coordination compounds, have found use as both therapeutic agents and tools for studying the importance of this ion channel. In this study, six Co 3 + cage compounds with sarcophagine-like ligands were assessed for their abilities to inhibit MCU-mediated mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Building upon these prior studies, we investigated a series of different cobalt amine complexes that led to the identification of promising candidates that can inhibit m Ca 2+ uptake in permeabilized cells with nanomolar potency (Figure 10). [63,73] These efforts revealed [Co(sen)] 3+ to be an MCU inhibitor that can operate in intact, non‐permeabilized cells [73] . In addition, docking and site‐directed mutagenesis studies revealed that these compounds most likely interact with the DXXE region of the MCU pore [63] .…”
Section: Other Metal‐based Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Building upon these prior studies, we investigated a series of different cobalt amine complexes that led to the identification of promising candidates that can inhibit m Ca 2+ uptake in permeabilized cells with nanomolar potency (Figure 10). [63,73] These efforts revealed [Co(sen)] 3+ to be an MCU inhibitor that can operate in intact, non‐permeabilized cells [73] . In addition, docking and site‐directed mutagenesis studies revealed that these compounds most likely interact with the DXXE region of the MCU pore [63] .…”
Section: Other Metal‐based Inhibitorsmentioning
confidence: 99%
“…[63,73] These efforts revealed [Co(sen)] 3 + to be an MCU inhibitor that can operate in intact, non-permeabilized cells. [73] In addition, docking and sitedirected mutagenesis studies revealed that these compounds most likely interact with the DXXE region of the MCU pore. [63] Thus, unsurprisingly, this critical motif appears to be a common target for most MCU inhibitors.…”
Section: Other Metal-based Inhibitorsmentioning
confidence: 99%
“…In comparison to NOTA and DOTA, Co-Sar stability/formation constants have not been measured due to their high kinetic inertness, 25 which makes Sar and Sar-derivatives interesting as stabilizers for Co. Additionally, the process to remove Co from Co-Sar complexes requires such stringent conditions that concentrated hydrochloric acid alone is insufficient to fully degrade the complex. 21,28 Given the high stability of Co-Sar complexes in vitro and in vivo, 19,29 along with recent studies highlighting unique biological applications of Co-Sar derivatives in vitro, 23 functionalized Sar compounds could therefore potentially be developed into promising Co-based radiopharmaceuticals. This work starts with an exploration of the labeling conditions for cyclotron-produced 55 Co with DiAmSar (DSar, a derivative of Sar), followed by in vitro/in vivo stability evaluation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Cobalt-55 ( t 1/2 = 17.53 h, I β+ = 77%) is quantifiable with positron emission tomography (PET) imaging and has demonstrated significant potential in preclinical oncology research. Cobalt-55 can also serve as a diagnostic congener for 58m Co ( t 1/2 = 9.10 h, IC = 100%), a low-energy electron-emitting radionuclide that holds promise for treating small metastatic disease due to its potential to reduce radiation dose to off-target tissues. , Despite Sar synthesis procedures typically beginning with Co-ethylenediamine complexation, we have not found prior reports of labeling Co to uncoordinated Sar complexes in no-carrier-added conditions. Most Co-radiopharmaceuticals have stabilized Co via 1,4,7-triazacyclononane-1,4,7-triacetic acid (NOTA) ,, and 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA). ,,,, NOTA can be radiolabeled with Co at room temperature and pH = 4–7, whereas DOTA typically requires additional heating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation